Repeated Uniaxial Compression Test of Permeable Friction Courses Mixtures under Seepage Field and Stress Field Coupling - Zhang Xingmei; Li Yarui; Yang Datian (Advances in Materials Science and Engineering)
In order to study the variations of the non-Darcy flow permeability coefficient and the porosity of permeable friction courses (PFCs), as well as the effects of the coupled seepage and stress fields on them, repeated uniaxial compression tests were carried out under the coupled action of water and a load. A set of water and load coupling tests were conducted, and a non-Darcy flow permeability coefficient tester was also made. After the PFC-13 specimen was carried out by the repeated uniaxial compression test under the water and load coupling, the total air void ratio and effective air void ratio were measured by the vacuum sealing method, and the non-Darcy flow permeability coefficients were obtained by a non-Darcy flow permeability coefficient tester. It was found that the coupled action of water and a load caused the total air void ratio, effective air void ratio, and permeability coefficient to sharply increase and reduced the number of repeated uniaxial compression cycles. These results are helpful for the design, construction, and maintenance of PFC mixtures.